Crystal Structure of PG16 and Chimeric Dissection with Somatically Related PG9: Structure-Function Analysis of Two Quaternary-Specific Antibodies That Effectively Neutralize HIV-1 - Pancera, Marie; McLellan, Jason S.; Wu, Xueling; Zhu, Jiang; Changela, Anita; Schmidt, Stephen D.; Yang, Yongping; Zhou, Tongqing; Phogat, Sanjay; Mascola, John R.; Kwong, Peter D. (Journal of Virology, 2010)
OA Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI